Glycoprotein C of herpes simplex virus type 1 plays a principal role in the adsorption of virus to cells and in infectivity. - Herold, B C (1991)
The purpose of this study was to identify the herpes simplex virus glycoprotein(s) that mediates the adsorption of virions to cells. Because heparan sulfate moieties of cell surface proteoglycans serve as the receptors for herpes simplex virus adsorption, we tested whether any of the viral glycoproteins could bind to heparin-Sepharose in affinity chromatography experiments. Two glycoproteins, gB and gC, bound to heparin-Sepharose and could be eluted with soluble heparin. In order to determine whether virions devoid of gC or gB were impaired for adsorption, we quantitated the binding of wild-type and mutant virions to cells. We found that at equivalent input concentrations of purified virions, significantly fewer gC-negative virions bound to cells than did wild-type or gB-negative virions. In addition, the gC-negative virions that bound to cells showed a significant delay in penetration compared with wild-type virus. The impairments in adsorption and penetration of the gC-negative virions can account for their reduced PFU/particle ratios, which were found to be about 5 to 10% that of wild-type virions, depending on the host cell. Although gC is dispensable for replication of herpes simplex virus in cell culture, it clearly facilitates virion adsorption and enhances infectivity by about a factor of 10.